Cationic modified soft PVC membrane material and preparation method thereof

By introducing a crosslinking network structure into soft PVC membrane materials, the problem of insufficient antibacterial and self-healing capabilities of traditional membrane materials is solved, and healthier and longer-lasting membrane performance is achieved.

CN119241976APending Publication Date: 2025-01-03NANTONG JIMEI DECORATION MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411601168.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional soft PVC membrane materials lack antibacterial properties and self-repair ability, and are prone to mold and breeding bacteria under the erosion of water stains, and cannot recover after being bumped and scratched, which affects service life and beauty.

Method used

The preparation method of cationically modified soft PVC film material is adopted to react materials such as premodified polyvinyl chloride, allyl salicyaldehyde Schiff base ligand, modified zinc oxide, bismaleimide ultraviolet absorber. , form a crosslinking network structure, imparting antibacterial and self-healing properties to the membrane material.

Benefits of technology

It improves the antibacterial performance and self-repair ability of the membrane material, extends the service life, and can be recombined and repaired through the crosslinking network structure after being damaged.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128350080000041
    Figure BDA0005128350080000041
  • Figure BDA0005128350080000051
    Figure BDA0005128350080000051
  • Figure BDA0005128350080000131
    Figure BDA0005128350080000131
Patent Text Reader

Abstract

The invention discloses a cation modified soft PVC membrane material and a preparation method thereof, and relates to the technical field of high polymer materials. When the cation modified soft PVC membrane material is prepared, pre-modified polyvinyl chloride and an allyl salicylaldehyde Schiff base ligand react to prepare modified polyvinyl chloride; the preparation method comprises the following steps: carrying out a reaction on 5-oxo-2, 3-dihydro-5H-thiazolo [3, 2-a] pyridine-3, 7-dicarboxylic acid and N-(2-ethoxyl) maleimide to prepare a bismaleimide ultraviolet absorbent; reacting the pre-modified zinc oxide with 2-chloromethyl furan to obtain modified zinc oxide; and mixing the modified polyvinyl chloride, the modified zinc oxide, a bismaleimide ultraviolet absorbent, zinc acetate, diisononyl phthalate, epoxidized soybean oil and calcium stearate, plastifying, calendering, cooling and rolling to prepare the cation modified soft PVC membrane material. The cation modified soft PVC membrane material prepared by the invention has excellent antibacterial, anti-aging and self-repairing properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a cation-modified soft PVC film material and a preparation method thereof. Background Art

[0002] Soft PVC film is a PVC film material with added plasticizer or softener. It has good thermal insulation and light transmittance, and is soft and easy to shape. Soft PVC is often used to make soft products such as plastic bags, plastic films, tablecloths, floors, etc. It can be used for home renovation, furniture stickers, waterproof and moisture-proof wallpaper, and various packaging materials, etc. It provides users with a rich selection of colors and patterns and is widely used in the decoration industry.

[0003] The soft PVC film materials prepared by traditional technology do not have antibacterial properties. Stickers, wallpapers, tablecloths, etc. will become moldy and breed bacteria under the erosion of water stains, which is harmful to people's health. In addition, these films will inevitably encounter bumps and scratches during use. Once damaged, they cannot be restored, which not only affects the appearance but also the service life. Based on the above problems, it is necessary to develop a new type of soft PVC film material to enhance the antibacterial ability of the film material and give the film material self-repairing properties, which is not only healthier and more hygienic, but also can extend the service life of the film material and save resources. Summary of the invention

[0004] The object of the present invention is to provide a cation-modified soft PVC film material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A cationic modified soft PVC membrane material, wherein the cationic modified soft PVC membrane material is prepared by reacting pre-modified polyvinyl chloride and allyl salicylaldehyde Schiff base ligand to obtain modified polyvinyl chloride; reacting pre-modified zinc oxide and 2-chloromethyl furan to obtain modified zinc oxide; and mixing modified polyvinyl chloride, modified zinc oxide, bismaleimide ultraviolet absorber, zinc acetate, diisononyl phthalate, epoxy soybean oil and calcium stearate, plasticizing, calendering, cooling and rolling to obtain the cationic modified soft PVC membrane material.

[0007] The allyl salicylaldehyde Schiff base ligand is prepared by reacting 2-hydroxy-4-allyloxybenzaldehyde and 2-furylmethylamine;

[0008] The pre-modified polyvinyl chloride is prepared by reacting polyvinyl chloride and sodium hydroxide;

[0009] The pre-modified zinc oxide is prepared by reacting zinc oxide and N,N-diethyl-3-aminopropyltriethoxysilane;

[0010] The bismaleimide ultraviolet absorber is prepared by reacting 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid and N-(2-hydroxyethyl)maleimide.

[0011] A method for preparing a cation-modified soft PVC film material, the method for preparing the cation-modified soft PVC film material comprising the following preparation steps:

[0012] (1) Polyvinyl chloride and sodium hydroxide aqueous solution are mixed in a mass ratio of 1:(0.1-0.12), stirred at 85-95°C and 300-500 r / min for 2-3 h, filtered, washed with deionized water for 3-5 times, and dried at 50-60°C for 10-12 h under vacuum conditions to obtain pre-modified polyvinyl chloride; pre-modified polyvinyl chloride, allyl salicylaldehyde Schiff base ligand, azobisisobutyronitrile, and cyclohexanone are mixed in a mass ratio of 1:(0.7-0.8):(0.01-0.03):(8-10), stirred at 70-80°C and 500-600 r / min for 3-4 h under nitrogen protection, cooled to room temperature, added with an equal volume of methanol of cyclohexanone, mixed, filtered, washed with methanol for 3-5 times, and dried at 50-60°C for 11-13 h under vacuum conditions to obtain modified polyvinyl chloride;

[0013] (2) 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and dichloromethane were mixed uniformly in a mass ratio of 1:(0.01-0.02):(0.03-0.05):(8-10), and stirred at 0-2°C and 300-500 r / min for 1-2 h under nitrogen protection. Add N-(2-hydroxyethyl)maleimide at a constant rate of 2 times the molar amount of 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid dropwise over 5 minutes, continue stirring and reacting for 20 to 24 hours under nitrogen protection, add an equal volume of dichloromethane and deionized water to mix evenly, let stand to separate, take the organic phase, and dry it at 30 to 40°C under vacuum for 20 to 24 hours to obtain a bismaleimide ultraviolet absorber;

[0014] (3) Mix zinc oxide and anhydrous ethanol in a mass ratio of 1:(50-60) and evenly, add silane hydrolyzate in an amount of 8-10 times the mass of zinc oxide, stir and react at 50-60°C and 300-500 r / min for 2-3 hours, filter, wash with anhydrous ethanol for 3-5 times, and dry at 50-60°C for 8-10 hours under vacuum conditions to obtain pre-modified zinc oxide; mix pre-modified zinc oxide, 2-chloromethylfuran, and toluene in a mass ratio of 1:(2-3):(40-50) and evenly, stir at 40-50°C and 300-500 r / min for 6-7 hours, filter, wash with anhydrous ethanol for 3-5 times, and dry at 50-60°C for 10-12 hours under vacuum conditions to obtain modified zinc oxide;

[0015] (4) Weigh 95-105 parts of modified polyvinyl chloride, 4-5 parts of modified zinc oxide, 6-8 parts of bismaleimide ultraviolet absorber, 0.6-1 part of zinc acetate, 16-18 parts of diisononyl phthalate, 2-3 parts of epoxy soybean oil, and 3-4 parts of calcium stearate by mass, place the mixture in a high-speed mixer, stir at 80-100° C. and 800-1000 r / min for 6-10 min, place the mixture in an internal mixer, stir at 155-165° C. and 600-800 r / min for 12-14 min, place the mixture in a calender for calendering, cool, and roll up to obtain a cationic modified soft PVC film.

[0016] As an optimization, the mass fraction of the sodium hydroxide aqueous solution in step (1) is 9% to 11%.

[0017] As an optimization, the model of the polyvinyl chloride in step (1) is SG-8.

[0018] As an optimization, the preparation method of the allyl salicylaldehyde Schiff base ligand in step (1) is: adding 2-hydroxy-4-allyloxybenzaldehyde and 2-furanmethylamine in a molar ratio of 1:1 to methanol 20 to 24 times the mass of 2-hydroxy-4-allyloxybenzaldehyde, stirring at 50 to 60°C and 300 to 500 r / min for 4 to 5 hours, and drying at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain the allyl salicylaldehyde Schiff base ligand;

[0019] The reaction process is:

[0020]

[0021] As an optimization, the reaction process of the bismaleimide UV absorber in step (2) is:

[0022]

[0023] As an optimization, the preparation method of the silane hydrolyzate in step (3) is: N, N-diethyl-3-aminopropyltriethoxysilane and anhydrous ethanol are mixed uniformly in a mass ratio of 1: (20-30), the pH is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10-30° C. and 300-500 r / min for 50-60 min to prepare a silane hydrolyzate.

[0024] As an optimization, the particle size of the zinc oxide in step (3) is 0.2 to 0.4 μm.

[0025] As an optimization, the process parameters of the calendering molding in step (4) are: setting the temperature of the calender to 160-170° C. and the speed to 18-20 m / min.

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0027] In the preparation of the cationic modified soft PVC film material, 2-hydroxy-4-allyloxybenzaldehyde and 2-furanmethylamine are reacted to obtain allyl salicylaldehyde Schiff base ligand; polyvinyl chloride and sodium hydroxide are reacted to obtain pre-modified polyvinyl chloride; pre-modified polyvinyl chloride and allyl salicylaldehyde Schiff base ligand are reacted to obtain modified polyvinyl chloride; 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid and N-(2-hydroxyethyl)maleic acid are reacted to obtain a 5-hydroxy-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid and N-(2-hydroxyethyl)maleic acid are reacted to obtain a 5-hydroxy-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid and a 5-hydroxy-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid and a 5-hydroxy-2,3-dihydro-5H-thiazol- ... The bismaleimide ultraviolet absorber is prepared by imide reaction; zinc oxide and N,N-diethyl-3-aminopropyltriethoxysilane are reacted to prepare pre-modified zinc oxide; pre-modified zinc oxide and 2-chloromethylfuran are reacted to prepare modified zinc oxide; modified polyvinyl chloride, modified zinc oxide, bismaleimide ultraviolet absorber, zinc acetate, diisononyl phthalate, epoxy soybean oil and calcium stearate are mixed, plasticized, calendered, cooled and rolled to prepare cationic modified soft PVC film material.

[0028] Firstly, the aldehyde group on 2-hydroxy-4-allyloxybenzaldehyde and the amino group on 2-furanmethylamine are subjected to Schiff base reaction to obtain allyl salicylaldehyde Schiff base ligand, and a carbon-carbon double bond and a furan group are introduced into the allyl salicylaldehyde Schiff base ligand; the allyl salicylaldehyde Schiff base ligand can form a coordination bond with the zinc ions in zinc acetate to form a cross-linked network structure, and can also recombine with the zinc ions escaped from zinc oxide after being damaged, thereby giving the cationic modified soft PVC film material excellent self-healing properties; polyvinyl chloride and sodium hydroxide are reacted to obtain pre-modified polyvinyl chloride, and the pre-modified polyvinyl chloride is A carbon-carbon double bond is introduced into the main chain of the ethylene molecule; pre-modified polyvinyl chloride and allyl salicylaldehyde Schiff base ligand are reacted to obtain modified polyvinyl chloride, the allyl salicylaldehyde Schiff base ligand is grafted onto the side chain of the modified polyvinyl chloride molecule through a free radical polymerization reaction, and a furan group is introduced into the side chain of the modified polyvinyl chloride molecule. The furan group introduced into the side chain of the modified polyvinyl chloride molecule can undergo a Diels-Alder addition reaction with the maleimide group on the bismaleimide UV absorber to form a thermally reversible cross-linked network structure, thereby giving the cationic modified soft PVC film material excellent self-healing properties.

[0029] Secondly, the carboxyl group on 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid is esterified with the hydroxyl group on N-(2-hydroxyethyl)maleimide to obtain a bismaleimide UV absorber; the pyridone structure on the bismaleimide UV absorber has strong absorption in the ultraviolet region, and converts solar energy into fluorescence and dissipates it, giving the cationic modified soft PVC film material excellent anti-aging properties, and the maleimide group on the bismaleimide UV absorber can undergo a Diels-Alder addition reaction with the furan group on modified polyvinyl chloride and modified zinc oxide to form a thermally reversible cross-linked network structure, giving the cationic modified soft PVC film material excellent self-healing properties.

[0030] Finally, zinc oxide and N,N-diethyl-3-aminopropyltriethoxysilane are reacted to obtain pre-modified zinc oxide, and a tertiary amine structure is introduced on the pre-modified zinc oxide; the tertiary amine structure on the pre-modified zinc oxide is reacted with the chlorine atom on 2-chloromethylfuran to obtain modified zinc oxide; a quaternary ammonium salt structure is generated on the modified zinc oxide, and a furan group is introduced; the quaternary ammonium salt structure can improve the antibacterial properties of the cation-modified soft PVC film, and the furan group can undergo a Diels-Alder addition reaction with the maleimide group on the bismaleimide UV absorber to form a thermally reversible cross-linked network structure, giving the cation-modified soft PVC film excellent self-healing properties; the addition of zinc oxide can not only improve the antibacterial properties of the cation-modified soft PVC film, but also when the cation-modified soft PVC film is damaged, the zinc ions released from the zinc oxide can recombine with the salicylaldehyde Schiff base ligand on the modified polyvinyl chloride to form new cross-linking sites, thereby achieving a self-healing effect. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] Embodiment 1:

[0033] A method for preparing a cation-modified soft PVC film material, the method for preparing the cation-modified soft PVC film material comprising the following preparation steps:

[0034] (1) 2-Hydroxy-4-allyloxybenzaldehyde and 2-furanylamine were added to methanol (20 times the mass of 2-hydroxy-4-allyloxybenzaldehyde) in a molar ratio of 1:1, stirred at 50°C and 300 r / min for 5 h, and dried at 50°C for 10 h under vacuum conditions to obtain an allyl salicylaldehyde Schiff base ligand; polyvinyl chloride and a 9% sodium hydroxide aqueous solution were mixed in a mass ratio of 1:0.1, stirred at 85°C and 300 r / min for 3 h, filtered, and removed by filtration. The pre-modified polyvinyl chloride was washed with water for 3 times, and dried at 50°C for 12 hours under vacuum conditions to obtain pre-modified polyvinyl chloride; the pre-modified polyvinyl chloride, allyl salicylaldehyde Schiff base ligand, azobisisobutyronitrile and cyclohexanone were mixed evenly in a mass ratio of 1:0.7:0.01:8, stirred at 70°C and 500r / min for 4 hours under nitrogen protection, cooled to room temperature, and an equal volume of cyclohexanone and methanol were added to mix evenly, filtered, washed with methanol for 3 times, and dried at 50°C for 13 hours under vacuum conditions to obtain modified polyvinyl chloride;

[0035] (2) 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and dichloromethane were mixed in a mass ratio of 1:0.01:0.03:8, stirred at 0°C and 300 r / min for 2 h under nitrogen protection, and N-(2-hydroxyethyl)maleimide in an amount twice the molar amount of 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid was added dropwise at a uniform rate within 5 min. The mixture was stirred and reacted for 24 h under nitrogen protection. An equal volume of dichloromethane and deionized water were added and mixed evenly. The mixture was allowed to stand for stratification, and the organic phase was taken and dried at 30°C for 24 h under vacuum conditions to obtain a bismaleimide ultraviolet absorber;

[0036] (3) N, N-diethyl-3-aminopropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:20, the pH was adjusted to 4 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 10°C and 300 r / min for 60 min to prepare a silane hydrolyzate; zinc oxide and anhydrous ethanol were mixed at a mass ratio of 1:50, 8 times the mass of zinc oxide was added to the silane hydrolyzate, and the mixture was stirred at 50°C and 300 r / min for 3 h, filtered, washed with anhydrous ethanol for 3 times, and dried at 50°C under vacuum for 10 h to obtain pre-modified zinc oxide; pre-modified zinc oxide, 2-chloromethylfuran, and toluene were mixed at a mass ratio of 1:2:40, stirred at 40°C and 300 r / min for 7 h, filtered, washed with anhydrous ethanol for 3 times, and dried at 50°C under vacuum for 12 h to obtain modified zinc oxide;

[0037] (4) 95 parts of modified polyvinyl chloride, 4 parts of modified zinc oxide, 6 parts of bismaleimide ultraviolet absorber, 0.6 parts of zinc acetate, 16 parts of diisononyl phthalate, 2 parts of epoxy soybean oil, and 3 parts of calcium stearate were weighed by mass, placed in a high-speed mixer, stirred at 80°C and 800 r / min for 10 min, placed in an internal mixer, stirred at 155°C and 600 r / min for 14 min, placed in a calender for calendering, set the calender temperature to 160°C and the speed to 18 m / min, cooled, and rolled to obtain a cationic modified soft PVC film.

[0038] Embodiment 2:

[0039] A method for preparing a cation-modified soft PVC film material, the method for preparing the cation-modified soft PVC film material comprising the following preparation steps:

[0040] (1) 2-Hydroxy-4-allyloxybenzaldehyde and 2-furanylamine were added to methanol (22 times the mass of 2-hydroxy-4-allyloxybenzaldehyde) in a molar ratio of 1:1, stirred at 55°C and 400 r / min for 4.5 hours, and dried at 55°C under vacuum for 9 hours to obtain an allyl salicylaldehyde Schiff base ligand; polyvinyl chloride and a 10% sodium hydroxide aqueous solution were mixed in a mass ratio of 1:0.11, stirred at 90°C and 400 r / min for 2.5 hours, and filtered to remove the residue. The pre-modified polyvinyl chloride was washed with deionized water for 4 times, and dried at 55°C for 11 hours under vacuum conditions to obtain pre-modified polyvinyl chloride; the pre-modified polyvinyl chloride, allyl salicylaldehyde Schiff base ligand, azobisisobutyronitrile and cyclohexanone were mixed evenly in a mass ratio of 1:0.75:0.02:9, stirred at 75°C and 550r / min for 3.5 hours under nitrogen protection, cooled to room temperature, and an equal volume of cyclohexanone and methanol were added to mix evenly, filtered, washed with methanol for 4 times, and dried at 55°C for 12 hours under vacuum conditions to obtain modified polyvinyl chloride;

[0041] (2) 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and dichloromethane were mixed in a mass ratio of 1:0.015:0.04:9, stirred at 1°C and 400 r / min for 1.5 h under nitrogen protection, and N-(2-hydroxyethyl)maleimide in an amount twice the molar amount of 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid was added dropwise at a uniform rate within 5 min. The mixture was stirred and reacted for 22 h under nitrogen protection. An equal volume of dichloromethane and deionized water were added and mixed evenly. The mixture was allowed to stand for stratification, and the organic phase was taken and dried at 35°C under vacuum for 22 h to obtain a bismaleimide ultraviolet absorber;

[0042] (3) N, N-diethyl-3-aminopropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:25, the pH was adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; zinc oxide and anhydrous ethanol were mixed at a mass ratio of 1:55, 9 times the mass of zinc oxide was added to the silane hydrolyzate, and the mixture was stirred at 55°C and 400 r / min for 2.5 h, filtered, washed with anhydrous ethanol 4 times, and dried at 55°C under vacuum for 9 h to obtain pre-modified zinc oxide; pre-modified zinc oxide, 2-chloromethylfuran, and toluene were mixed at a mass ratio of 1:2.5:45, stirred at 45°C and 400 r / min for 6.5 h, filtered, washed with anhydrous ethanol 4 times, and dried at 55°C under vacuum for 11 h to obtain modified zinc oxide;

[0043] (4) 100 parts of modified polyvinyl chloride, 4.5 parts of modified zinc oxide, 7 parts of bismaleimide ultraviolet absorber, 0.8 parts of zinc acetate, 17 parts of diisononyl phthalate, 2.5 parts of epoxy soybean oil, and 3.5 parts of calcium stearate were weighed by mass, placed in a high-speed mixer, stirred at 90°C and 900 r / min for 8 min, placed in an internal mixer, stirred at 160°C and 700 r / min for 13 min, placed in a calender for calendering, set the calender temperature to 165°C and the speed to 19 m / min, cooled, and rolled up to obtain a cationic modified soft PVC film.

[0044] Embodiment 3:

[0045] A method for preparing a cation-modified soft PVC film material, the method for preparing the cation-modified soft PVC film material comprising the following preparation steps:

[0046] (1) 2-Hydroxy-4-allyloxybenzaldehyde and 2-furanylamine were added to methanol (24 times the mass of 2-hydroxy-4-allyloxybenzaldehyde) in a molar ratio of 1:1, stirred at 60°C and 500 r / min for 4 hours, and dried at 60°C for 8 hours under vacuum conditions to obtain an allyl salicylaldehyde Schiff base ligand; polyvinyl chloride and a sodium hydroxide aqueous solution with a mass fraction of 11% were mixed in a mass ratio of 1:0.12, stirred at 95°C and 500 r / min for 2 hours, filtered, and removed by filtration. The pre-modified polyvinyl chloride was washed with water for 5 times, and dried at 60°C for 10 hours under vacuum conditions to obtain pre-modified polyvinyl chloride; the pre-modified polyvinyl chloride, allyl salicylaldehyde Schiff base ligand, azobisisobutyronitrile and cyclohexanone were mixed evenly in a mass ratio of 1:0.8:0.03:10, stirred at 80°C and 600r / min for 3 hours under nitrogen protection, cooled to room temperature, and an equal volume of cyclohexanone and methanol were added to mix evenly, filtered, washed with methanol for 5 times, and dried at 60°C for 11 hours under vacuum conditions to obtain modified polyvinyl chloride;

[0047] (2) 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and dichloromethane were mixed in a mass ratio of 1:0.02:0.05:10, stirred at 2°C and 500 r / min for 1 hour under nitrogen protection, and N-(2-hydroxyethyl)maleimide in an amount twice the molar amount of 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid was added dropwise at a uniform rate within 5 minutes. The mixture was stirred and reacted for 20 hours under nitrogen protection, and an equal volume of dichloromethane and deionized water were added to mix the mixture evenly. The mixture was allowed to stand for stratification, and the organic phase was taken and dried at 40°C for 20 hours under vacuum conditions to obtain a bismaleimide ultraviolet absorber;

[0048] (3) N, N-diethyl-3-aminopropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:30, the pH was adjusted to 6 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 30°C and 500 r / min for 50 min to prepare a silane hydrolyzate; zinc oxide and anhydrous ethanol were mixed at a mass ratio of 1:60, 10 times the mass of zinc oxide was added to the silane hydrolyzate, and the mixture was stirred at 60°C and 500 r / min for 2 h, filtered, washed with anhydrous ethanol for 5 times, and dried at 60°C under vacuum for 8 h to obtain pre-modified zinc oxide; pre-modified zinc oxide, 2-chloromethylfuran, and toluene were mixed at a mass ratio of 1:3:50, stirred at 50°C and 500 r / min for 6 h, filtered, washed with anhydrous ethanol for 5 times, and dried at 60°C under vacuum for 10 h to obtain modified zinc oxide;

[0049] (4) 105 parts of modified polyvinyl chloride, 5 parts of modified zinc oxide, 8 parts of bismaleimide ultraviolet absorber, 1 part of zinc acetate, 18 parts of diisononyl phthalate, 3 parts of epoxy soybean oil, and 4 parts of calcium stearate were weighed by mass, placed in a high-speed mixer, stirred at 100°C and 1000 r / min for 6 min, placed in an internal mixer, stirred at 165°C and 800 r / min for 12 min, placed in a calender for calendering, set the calender temperature to 170°C and the speed to 20 m / min, cooled, and rolled up to obtain a cationic modified soft PVC film.

[0050] Comparative Example 1:

[0051] The preparation method of the cation-modified soft PVC film material of Comparative Example 1 is different from that of Example 2 in that step (1) is not performed, and step (4) is modified as follows: 100 parts of polyvinyl chloride, 4.5 parts of modified zinc oxide, 7 parts of bismaleimide ultraviolet absorber, 0.8 parts of zinc acetate, 17 parts of diisononyl phthalate, 2.5 parts of epoxy soybean oil, and 3.5 parts of calcium stearate are weighed by mass, placed in a high-speed mixer, stirred at 90°C and 900r / min for 8min, placed in an internal mixer, stirred at 160°C and 700r / min for 13min, placed in a calender for calendering, the calender temperature is set to 165°C, the speed is set to 19m / min, cooled, and rolled to obtain a cation-modified soft PVC film material. The remaining steps are the same as those of Example 2.

[0052] Comparative Example 2:

[0053] The preparation method of the cation-modified soft PVC film material of Comparative Example 2 is different from that of Example 2 in that step (2) is not performed, and step (4) is modified as follows: 100 parts of modified polyvinyl chloride, 4.5 parts of modified zinc oxide, 0.8 parts of zinc acetate, 17 parts of diisononyl phthalate, 2.5 parts of epoxy soybean oil, and 3.5 parts of calcium stearate are weighed by mass, placed in a high-speed mixer, stirred at 90°C and 900r / min for 8min, placed in an internal mixer, stirred at 160°C and 700r / min for 13min, placed in a calender for calendering, the calender temperature is set to 165°C, the speed is set to 19m / min, cooled, and rolled to obtain a cation-modified soft PVC film material. The remaining steps are the same as those of Example 2.

[0054] Comparative Example 3:

[0055] The preparation method of the cation-modified soft PVC film material of Comparative Example 3 is different from that of Example 2 only in that step (3) is not performed, and step (4) is modified as follows: 100 parts of modified polyvinyl chloride, 7 parts of bismaleimide ultraviolet absorber, 0.8 parts of zinc acetate, 17 parts of diisononyl phthalate, 2.5 parts of epoxy soybean oil, and 3.5 parts of calcium stearate are weighed by mass, placed in a high-speed mixer, stirred at 90°C and 900r / min for 8min, placed in an internal mixer, stirred at 160°C and 700r / min for 13min, placed in a calender for calendering, the calender temperature is set to 165°C, the speed is set to 19m / min, cooled, and rolled to obtain a cation-modified soft PVC film material. The remaining steps are the same as those of Example 2.

[0056] Comparative Example 4:

[0057] The preparation method of the cationic modified soft PVC film material of Comparative Example 4 is different from that of Example 2 only in that step (3) is not performed, and step (4) is modified as follows: 100 parts of modified polyvinyl chloride, 4.5 parts of zinc oxide, 7 parts of bismaleimide UV absorber, 0.8 parts of zinc acetate, 17 parts of diisononyl phthalate, 2.5 parts of epoxy soybean oil, and 3.5 parts of calcium stearate are weighed by mass, placed in a high-speed mixer, stirred at 90°C and 900 r / min for 8 minutes, placed in an internal mixer, stirred at 160°C and 700 r / min for 13 minutes, placed in a calender for calendering, the calender temperature is set to 165°C, the speed is set to 19 m / min, cooled, and rolled to obtain a cationic modified soft PVC film material.

[0058] Test Example 1

[0059] Antimicrobial performance testing

[0060] Test method: The examples and comparative examples were cut into 10 mm × 10 mm samples and sterilized by ultraviolet irradiation for 3 h; the Escherichia coli strains were activated and prepared to a concentration of 3 × 10 4 cfu / ml bacterial suspension; put the sample into the bacterial suspension, shake at 300r / min for 5min at room temperature, take 1ml of the bacterial suspension and dilute it to 100 times, take 1ml of the diluted bacterial suspension and inoculate it into agar medium, culture it at 37℃ for 16h, count the colonies according to the method in GB / T15979, and calculate the antibacterial rate. The results are shown in Table 1.

[0061] Table 1

[0062] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.87 Comparative Example 1 99.76 Example 2 99.91 Comparative Example 2 99.80 Example 3 99.85 Comparative Example 3 76.28 Comparative Example 4 88.14

[0063] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the cationic modified soft PVC film material prepared in the present invention has good antibacterial properties.

[0064] By comparison, the antibacterial rates of Examples 1 to 3 are greater than those of Comparative Examples 3 to 4, and the antibacterial rate of Comparative Example 4 is greater than that of Comparative Example 3, indicating that the addition of zinc oxide can improve the antibacterial properties of the cation-modified soft PVC film material; zinc oxide and N,N-diethyl-3-aminopropyltriethoxysilane are reacted to obtain pre-modified zinc oxide, and a tertiary amine structure is introduced into the pre-modified zinc oxide; the tertiary amine structure on the pre-modified zinc oxide is reacted with the chlorine atom on 2-chloromethylfuran to obtain modified zinc oxide, and a quaternary ammonium salt structure is generated on the modified zinc oxide; the quaternary ammonium salt structure can further improve the antibacterial properties of the cation-modified soft PVC film material.

[0065] Test Example 2

[0066] Anti-aging performance test

[0067] Test method: The embodiments and comparative examples were prepared into standard specimens according to GB / T1040, and their tensile strength was tested. The standard specimens were irradiated with a xenon arc lamp for 5 days, and their tensile strength was tested. The change rate of the tensile strength of the embodiments and comparative examples before and after ultraviolet aging treatment was calculated, and the change rate of tensile strength = (original tensile strength of the specimen - tensile strength after ultraviolet aging treatment) / original tensile strength of the specimen × 100%. The results are shown in Table 2.

[0068] Table 2

[0069]

[0070] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the cationic modified soft PVC film material prepared in the present invention has good anti-aging performance.

[0071] By comparison, the change rate of tensile strength of Examples 1 to 3 is less than that of Comparative Example 2, indicating that the carboxyl group on 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid is esterified with the hydroxyl group on N-(2-hydroxyethyl)maleimide to obtain the bismaleimide ultraviolet absorber; the pyridone structure on the bismaleimide ultraviolet absorber has strong absorption in the ultraviolet region, and converts solar energy into fluorescence and dissipates it; the maleimide group on the bismaleimide ultraviolet absorber can undergo Diels-Alder addition reaction with the furan group on modified polyvinyl chloride and modified zinc oxide to form a cross-linked network, fix the small molecule ultraviolet absorber on the polyvinyl chloride molecular chain, prevent the precipitation of the ultraviolet absorber, and give the cationic modified soft PVC film material excellent anti-aging properties.

[0072] Test Example 3

[0073] Self-healing performance test

[0074] Test method: According to GB / T1040, the embodiment and the comparative example are cut into standard specimens, and their original tensile strength is tested by a tensile machine. A slit with a depth of 2 mm and a length of 10 mm is cut from the middle of the standard specimen, and the specimen is placed in a mold, kept at 70°C for 4 hours, and left to stand at room temperature for 36 hours to obtain the repaired specimen. The tensile strength is tested by a tensile machine. The self-repair rate of the embodiment and the comparative example is calculated, and the self-repair rate = (tensile strength of the repaired standard specimen / original tensile strength of the standard specimen) × 100%. The results are shown in Table 3.

[0075] Table 3

[0076] Self-repair rate (%) Self-repair rate (%) Example 1 97.57 Comparative Example 1 54.15 Example 2 98.26 Comparative Example 2 82.71 Example 3 98.11 Comparative Example 3 87.25 Comparative Example 4 94.15

[0077] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the cationic modified soft PVC film material prepared in the present invention has good self-repairing performance.

[0078] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that the aldehyde group on 2-hydroxy-4-allyloxybenzaldehyde and the amino group on 2-furanmethylamine are subjected to Schiff base reaction to obtain allyl salicylaldehyde Schiff base ligand, and carbon-carbon double bonds and furan groups are introduced into the allyl salicylaldehyde Schiff base ligand; the allyl salicylaldehyde Schiff base ligand can be recombined with zinc ions escaped from zinc oxide after being damaged, thereby giving the cationic modified soft PVC film material excellent self-repairing properties; polyvinyl chloride and sodium hydroxide are reacted to obtain pre-modified polyvinyl chloride, and the pre-modified polyvinyl chloride is A carbon-carbon double bond is introduced into the main chain of the olefin molecule; pre-modified polyvinyl chloride and allyl salicylaldehyde Schiff base ligand are reacted to obtain modified polyvinyl chloride, the allyl salicylaldehyde Schiff base ligand is grafted onto the side chain of the modified polyvinyl chloride molecule through a free radical polymerization reaction, and a furan group is introduced into the side chain of the modified polyvinyl chloride molecule. The furan group introduced into the side chain of the modified polyvinyl chloride molecule can undergo a Diels-Alder addition reaction with the maleimide group on the bismaleimide UV absorber to form a thermally reversible cross-linked network structure, thereby further improving the self-healing properties of the cationically modified soft PVC film material.

[0079] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that the carboxyl group on 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid is esterified with the hydroxyl group on N-(2-hydroxyethyl)maleimide to obtain a bismaleimide UV absorber; the maleimide group on the bismaleimide UV absorber can undergo a Diels-Alder addition reaction with the furan group on the modified polyvinyl chloride and modified zinc oxide to form a thermally reversible cross-linked network structure, thereby giving the cationic modified soft PVC film material excellent self-repairing properties.

[0080] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that the addition of zinc oxide can allow the zinc ions released from the zinc oxide to recombine with the salicylaldehyde Schiff base ligands on the modified polyvinyl chloride when the cationic modified soft PVC film is damaged, thereby forming new cross-linking sites and achieving a self-repairing effect.

[0081] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 4, indicating that zinc oxide and N,N-diethyl-3-aminopropyltriethoxysilane are reacted to obtain pre-modified zinc oxide, and a tertiary amine structure is introduced into the pre-modified zinc oxide; the tertiary amine structure on the pre-modified zinc oxide reacts with the chlorine atom on 2-chloromethylfuran to obtain modified zinc oxide; a furan group is introduced into the modified zinc oxide; the furan group can undergo a Diels-Alder addition reaction with the maleimide group on the bismaleimide UV absorber to form a thermally reversible cross-linked network structure, thereby giving the cationic modified soft PVC film material excellent self-repairing properties.

[0082] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A cationic modified soft PVC film material, characterized in that: The cationic modified soft PVC membrane material is prepared by reacting pre-modified polyvinyl chloride and allyl salicylaldehyde Schiff base ligand to obtain modified polyvinyl chloride; The pre-modified zinc oxide and 2-chloromethylfuran are reacted to obtain the modified zinc oxide; The modified polyvinyl chloride, modified zinc oxide, bismaleimide ultraviolet absorber, zinc acetate, diisononyl phthalate, epoxy soybean oil and calcium stearate are mixed, plasticized, calendered, cooled and rolled to obtain the product; The allyl salicylaldehyde Schiff base ligand is prepared by reacting 2-hydroxy-4-allyloxybenzaldehyde and 2-furylmethylamine; The pre-modified polyvinyl chloride is prepared by reacting polyvinyl chloride and sodium hydroxide; The pre-modified zinc oxide is prepared by reacting zinc oxide and N,N-diethyl-3-aminopropyltriethoxysilane; The bismaleimide ultraviolet absorber is prepared by reacting 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid and N-(2-hydroxyethyl)maleimide.

2. A method for preparing a cationic modified soft PVC film material, characterized in that: The preparation method of the cationic modified soft PVC film material comprises the following preparation steps: (1) Polyvinyl chloride and sodium hydroxide aqueous solution are mixed in a mass ratio of 1:(0.1-0.12), stirred at 85-95°C and 300-500 r / min for 2-3 h, filtered, washed with deionized water for 3-5 times, and dried at 50-60°C for 10-12 h under vacuum conditions to obtain pre-modified polyvinyl chloride; pre-modified polyvinyl chloride, allyl salicylaldehyde Schiff base ligand, azobisisobutyronitrile, and cyclohexanone are mixed in a mass ratio of 1:(0.7-0.8):(0.01-0.03):(8-10), stirred at 70-80°C and 500-600 r / min for 3-4 h under nitrogen protection, cooled to room temperature, added with an equal volume of methanol of cyclohexanone, mixed, filtered, washed with methanol for 3-5 times, and dried at 50-60°C for 11-13 h under vacuum conditions to obtain modified polyvinyl chloride; (2) 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and dichloromethane were mixed uniformly in a mass ratio of 1:(0.01-0.02):(0.03-0.05):(8-10), and stirred at 0-2°C and 300-500 r / min for 1-2 h under nitrogen protection. Add N-(2-hydroxyethyl)maleimide at a constant rate of 2 times the molar amount of 5-oxo-2,3-dihydro-5H-thiazolo[3,2-a]pyridine-3,7-dicarboxylic acid dropwise over 5 minutes, continue stirring and reacting for 20 to 24 hours under nitrogen protection, add an equal volume of dichloromethane and deionized water to mix evenly, let stand to separate, take the organic phase, and dry it at 30 to 40°C under vacuum for 20 to 24 hours to obtain a bismaleimide ultraviolet absorber; (3) zinc oxide and anhydrous ethanol are mixed uniformly at a mass ratio of 1:(50-60), silane hydrolyzate of 8-10 times the mass of zinc oxide is added, stirring at 50-60° C. and 300-500 r / min for 2-3 h, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 50-60° C. for 8-10 h under vacuum conditions to obtain pre-modified zinc oxide; Pre-modified zinc oxide, 2-chloromethylfuran and toluene are mixed uniformly in a mass ratio of 1:(2-3):(40-50), stirred at 40-50°C and 300-500 r / min for 6-7 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 50-60°C for 10-12 hours under vacuum conditions to obtain modified zinc oxide; (4) Weigh 95-105 parts of modified polyvinyl chloride, 4-5 parts of modified zinc oxide, 6-8 parts of bismaleimide ultraviolet absorber, 0.6-1 part of zinc acetate, 16-18 parts of diisononyl phthalate, 2-3 parts of epoxy soybean oil, and 3-4 parts of calcium stearate by mass, place the mixture in a high-speed mixer, stir at 80-100° C. and 800-1000 r / min for 6-10 min, place the mixture in an internal mixer, stir at 155-165° C. and 600-800 r / min for 12-14 min, place the mixture in a calender for calendering, cool, and roll up to obtain a cationic modified soft PVC film.

3. The method for preparing a cationic modified soft PVC film material according to claim 2, characterized in that: The mass fraction of the sodium hydroxide aqueous solution in step (1) is 9% to 11%.

4. The method for preparing a cationic modified soft PVC film material according to claim 2, characterized in that: The model of the polyvinyl chloride in step (1) is SG-8.

5. The method for preparing a cationic modified soft PVC film material according to claim 2, characterized in that: The preparation method of the allyl salicylaldehyde Schiff base ligand in step (1) is as follows: 2-hydroxy-4-allyloxybenzaldehyde and 2-furanmethylamine are added in a molar ratio of 1:1 to methanol with a mass 20 to 24 times that of 2-hydroxy-4-allyloxybenzaldehyde, and the mixture is stirred at 50 to 60°C and 300 to 500 r / min for 4 to 5 hours, and dried at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain the allyl salicylaldehyde Schiff base ligand.

6. The method for preparing a cation-modified soft PVC film material according to claim 2, characterized in that: The preparation method of the silane hydrolyzate in step (3) is as follows: N, N-diethyl-3-aminopropyltriethoxysilane and anhydrous ethanol are mixed uniformly in a mass ratio of 1: (20-30), the pH is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10-30° C. and 300-500 r / min for 50-60 min to prepare a silane hydrolyzate.

7. The method for preparing a cation-modified soft PVC film material according to claim 2, characterized in that: The particle size of the zinc oxide in step (3) is 0.2 to 0.4 μm.

8. The method for preparing a cation-modified soft PVC film material according to claim 2, characterized in that: The process parameters of the calendering molding in step (4) are: setting the temperature of the calender to 160-170° C. and the speed to 18-20 m / min.

Citation Information

Cited By

  • High-barrier-property food packaging material and preparation process thereof

    CN118752876A

  • Special repairing adhesive sticker for salt pond covering film, preparation method and application thereof

    CN121610199A